Implementasi Pendidikan Inklusif Di Sekolah Dasar Dalam Mendukung Keberagaman Kebutuhan Belajar Peserta Didik - Sultoni Alparij; Muhammad Fauzan Muttaqin (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This Inclusive education is an important approach in elementary schools to ensure equal learning opportunities for all students, including those with diverse learning needs. Despite its significance, the implementation of inclusive education in elementary schools still faces various challenges related to instructional practices, teacher readiness, and institutional support. This study aims to examine the implementation of inclusive education in elementary schools based on existing literature. This research employed a literature review method by analyzing scholarly articles, books, and relevant policy documents related to inclusive education at the elementary school level. The literature was selected through systematic searching and screening processes to identify studies that discuss concepts, strategies, challenges, and best practices in implementing inclusive education. The results of the review indicate that the implementation of inclusive education in elementary schools generally involves adaptive teaching strategies, differentiated instruction, collaboration among teachers, and the provision of supportive learning environments. However, several studies highlight persistent obstacles, including limited teacher competence, inadequate facilities, and insufficient professional development programs. In conclusion, the implementation of inclusive education in elementary schools requires comprehensive support from teachers, schools, and policymakers. Strengthening teacher competencies and improving institutional readiness are essential to enhance inclusive educational practices. This literature review contributes to a deeper understanding of inclusive education implementation and provides recommendations for improving inclusive learning in elementary schools.